Mosaic installation tool / Juliyana Hussin … [et al.] - Hussin, Juliyana; Mohd Yazid, Mohd Zulfadli; Bachok@Nong Chik, Mohd Noor Hafiz; Mohd Yusof, Siti Natasha; Mohd Esa, Nor Faizah (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Our Mosaic Installation tools are designed to install the tiles more easily, accurately and neatly. This Mosaic Installation Tool is also used by less skilled workers and can reduce installation labour. This tool can be used in homes, for example in the living room, bathroom, kitchen and garage. In addition, this tool can also be used in small buildings. These Mosaic Installation tool can facilitate the labour force install mosaic with easier and faster. The materials used in this kit are like glass suet ton and spirit level. The purpose of the research conducts to design and produce smart installation tools. This mosaic installation tool will help the unskilled worker get more easily to install the mosaic. It also can improve the efficiency of the installation work. In addition, these tools can reduce waste cement, thus helping to reduce the cost of construction. This tool is also very easy to use and easy to carry when making installation work. In addition, by using this tool mosaic installation is tidier. Mosaic Installation tool is the right tool in the production of Installation work. Suitable Mosaic Installation Tools for construction that is small and aim learning. With item addition the rest, facilitate further usage Mosaic Installation Tools in future time. Result of respondent from questionnaire. Questionnaire is divided into two sections. Section A is a general question and Section B involve Mosaic Installation Tool's question.